Alumina ativada modificada por ozonização: preparação, caracterização e aplicação na remoção de íons fluoreto presentes em água subterrânea - Paula, Nátalie de (2021)
Fluoride concentration in drinking water is an important parameter to be monitored. At concentrations between 0.6 and 1.5 mg L-¹, it promotes an improvement in population oral health, preventing tooth decay. However, the long-term consumption of water containing fluoride concentrations higher than 1.5 mg L-¹ may cause dental and bone fluorosis and, in more severe cases, osteoporosis and other serious health problems. Despite this, many communities have been supplied with water containing values higher than those established by drinking standards. This fact occurs due to water scarcity caused by geographic location, low rainfall volumes, and lack of planning and management of water resources. Aiming water defluoridation, several treatment methods are studied, tested, and used around the world. These techniques are based on principles of precipitation-coagulation, ion exchange, electrodialysis, adsorption, and membrane separation processes. Among these techniques, adsorption stands out due to its ease of operation, high fluoride removal efficiency even at low concentrations, and a wide variety of available adsorbents. Aluminum-based adsorbents stand out in fluoride removal due to the high affinity between these elements. This way activated alumina is one of the most applied adsorbents for water defluoridation. Additionally, due to its low cost, it is widely used in industrial processes. Nevertheless, this material has some limitations that interfere with its performance. The water pH must be less than 6.0 to achieve high levels of fluoride removal. The pH of groundwater, however, varies between 5.5 and 8.5. The main goal of the present work was to modify the activated alumina surface (AA) through the ozonation technique and to evaluate the influence of this treatment on the material's ability to remove fluoride ions. The physicochemical properties of ozonated activated alumina (AAO) were determined through several analytical methods (SEM, EDX, XRD, FTIR, BET, NMR, PZ, and pHpzc). All experiments were conducted on a batch scale. It was verified that the AAO fluoride adsorption capacity was higher than the AA in all the conditions in which modifications were made. The parameter that most affected the surface modification was the AA concentration in the reaction medium. Comparatively, the AAO (obtained in the best condition) reached 98.3% of fluoride removal against 77.4% reached by the AA. Through experimental planning, it was identified that the highest fluoride removal occurred by using 4.35 g L-¹ of AAO and a pH of 8.0. Through equilibrium studies, it was found that the AAO maximum adsorption capacity was 15.80 mg g-¹. The most suitable isotherm model was the Sips model, in which it was obtained qms of 15.80 mg g-¹. Among the kinetic models, the general order model was the one that best fitted experimental data. It was verified, through thermodynamic analysis, a predominance of chemisorption phenomena and endothermic process, obtaining ΔG° of -10.73 kJ mol-¹, ΔH° of 312.07 kJ mol-¹, ΔS° of 1.54 kJ mol-¹. The results showed that, the modification of activated alumina by using the ozonation process was effective since it provided to the new adsorbent material a greater adsorption capacity for removing fluoride ions. Another important point to be highlighted is that the AA fluoride removal kinetic increased considerably after the modification with ozone. Finally, AA and AAO were applied to remove fluoride ions from an actual groundwater sample. In this condition, both materials showed a reduction in fluoride adsorption capacity, however, AAO was still more efficient (50.9%) than AA (16,9%).